2002
DOI: 10.1021/ac015629e
|View full text |Cite
|
Sign up to set email alerts
|

Scintillation Proximity Assay Using Molecularly Imprinted Microspheres

Abstract: Molecularly imprinted microspheres were prepared as antibody binding mimics and used in scintillation proximity assay of a beta-adrenergic antagonist, (S)-propranolol. By using small polymer beads, we were able to place an organic scintillator and an "antenna" component in close proximity to the imprinted binding sites. When the radioactive template bound to the polymer, radiation energy was effectively transferred, via the antenna component, to the scintillator to generate a fluorescence signal. Using molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…In this manner, near-monodispersed spherical beads can be prepared, and size and porosity can be fine-tuned thereby changing the polymerization conditions. This technique has been reported in MIP-based competition assays [71][72] and capillary electrochromatography [73][74], but only recently works have been published, in which it is clearly shown that precipitation polymerization can be a potentially fruitful technique for preparing chromatography-grade molecularly imprinted beads [75].…”
Section: Precipitation Polymerizationmentioning
confidence: 99%
“…In this manner, near-monodispersed spherical beads can be prepared, and size and porosity can be fine-tuned thereby changing the polymerization conditions. This technique has been reported in MIP-based competition assays [71][72] and capillary electrochromatography [73][74], but only recently works have been published, in which it is clearly shown that precipitation polymerization can be a potentially fruitful technique for preparing chromatography-grade molecularly imprinted beads [75].…”
Section: Precipitation Polymerizationmentioning
confidence: 99%
“…By incorporating an appropriate scintillation reporter element, MIPs can be designed to directly generate a specific physicochemical signal upon binding of an analyte. In Figure 6, the principle of of using a "universal" scintillation reporter embedded in molecularly imprinted microspheres is reported (Ye & Mosbach, 2001c;Ye et al, 2002). The MIP containing the scintillation reporter is imprinted against a -adrenergic antagonist, S-propranolol.…”
Section: Mip As Artificial Receptors and Antibodiesmentioning
confidence: 99%
“…In competitive mode, the non-labeled S-propranolol displaces the [3H]S-propranolol, and so reduces the fluorescence signal. Adapted from Ye et al, 2002. Imprinted-polymer-based assays are conveniently performed using radiolabels, because the labelled analyte has the same structure as the original template. However, this involves the handling of radioactive materials and produces radioactive waste, which is sometimes undesirable.…”
Section: Mip As Artificial Receptors and Antibodiesmentioning
confidence: 99%
“…Following this concept, we have developed a competitive scintillation proximity assay using a radiolabeled template as the probe. The imprinted scintillation polymers could be used in both organic and aqueous solvents [21]. "ANTI-IDIOTYPIC IMPRINTING" AND "DIRECT MOLDING": THE NEXT GENERATION Until now, most research activities have focused on generating imprinted materials recognizing different target entities ranging from small molecules to proteins [22,23], and, even to whole cells [24].…”
Section: Imprinted Scintillation Polymers: a New Sensor Conceptmentioning
confidence: 99%